Exploring an EAP writing teacher's adaptive expertise and adaptive teaching practices from a CDST perspective - Xiang, Xiaoting; Chang, Pengyun; Yu, Baohua (Frontiers in Psychology, 2022)
Teachers' adaptive expertise (TAE) has received increasing attention in the current English as foreign language (EFL) teaching field, however, it has seldom been examined with adaptive practices by teachers in on-going classes among existing literature. Adopting a mixed-method design with data triangulation, this study was conducted to explore the complexity of teachers' adaptive expertise (TAE) and adaptive teaching practices that an EAP writing teacher demonstrated in academic writing courses, from a Complex Dynamic Systems Theory (CDST) perspective. Semi-structured interviews, classroom observations, and questionnaires were arranged to collect qualitative and quantitative data from an EAP writing teacher and 43 EFL learners in a Chinese university. Thematic analysis and SPSS were mainly used in the current work for data analysis. Our findings confirmed (1) the complexity of TAE and ATP with specific features of non-linearity, interconnectedness, and self-organization, which are classic CDST characteristics; (2) the TAE evolved with meta-cognitive, cognitive, affective and social components that are intertwined and contributed to the teacher's adaptive teaching practices (ATP) in her academic writing course; (3) being facilitated by TAE, the teacher's adaptive teaching practices significantly enhanced EFL learners, learning motivation of academic writing and their learning efficiency. Findings of the current work pave the way for future studies in researching TAE and ATP with a thorough consideration of language teachers, students and contexts from the CDST perspective. Moreover, pedagogical contributions are highlighted through the detailed examinations of the EAP writing teacher's ATP, including the class design, teaching plans, and methods, which would be fruitful for the development of tertiary EAP writing research.